POLITICAL MARKETING AND IMPORTANCE MARKET CONTEXT IN INDONESIA REGIONAL ELECTION: An Analysis on Regional Election of Takalar 2017 - Sukri, Sukri (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2017)
The winning of Syamsari Kitta-Achmad Dg Se’re (SK-HD) against the incumbent Burhanuddin B - Natsir Ibrahim (Bur-Nojeng) was quite suprising in 2017 Local Election of Takalar Regency. Since the incumbent couple was believed to be in the ‘safe seat’ during the election. Based on several surveys and supported by many political parties, the incumbent couple was predicted to effortlessly win the election. The final result, however, showed that the new candidate was the winner despite being limitedly supported by merely three political parties. One factor which had seemingly been as the main winning strategy was to maximize the couple’s political marketing. This study aims to describe the political marketing strategy undertaken by the winning candidates of SK-HD in the 2017 Takalar local election. Using qualitative research, the results of this study indicate that the winning of SK-HD was based on several aspects. These may include the mixture of the candidate’s social, political and economical assets, coupled with the existing socio-political context of Takalar and of South Sulawesi Province, and the marketing strategy which had vividly and thoroughly been executed by their teamwork.